Petrogenesis and deformation history of the lawsonite‐bearing blueschist facies metabasalts of the Diamante‐Terranova oceanic unit (southern Italy). (31st January 2018) - Fedele, L.; Tramparulo, F. D'A.; Vitale, S.; Cappelletti, P.; Prinzi, E. P.; Mazzoli, S.
Abstract: The Neotethyan oceanic Diamante‐Terranova unit (DIATU; southern Apennines–Calabria–Peloritani Terrane system) includes basic rocks that during the Cenozoic were subducted and metamorphosed to lawsonite‐blueschist facies conditions. Petrological and structural observations (both at the meso‐ and micro‐scale) show that lawsonite growth was continuous during three distinctive ductile deformation stages (D1–D3). These likely occurred close to the metamorphic peak, estimated at 350–390°C and 0.9–1.1 GPa, producing an equilibrium assemblage made of blue Na‐amphibole, lawsonite, chlorite and pumpellyite. Locally, pods dominated by quartz and epidote (plus chlorite, calcite and green Ca‐amphibole) developed at similar conditions (350–370°C, 0.8–0.9 GPa). Post‐peak evolution during the final exhumation of the DIATU along the subduction channel, also consisted of three deformation stages, defined by folding (D4) and normal faulting (D5) and finally by strike‐slip faulting (D6), affecting both the blueschist unit and the unconformably overlying Tortonian conglomerates. Vorticity analysis on syn‐tectonic lawsonite crystals indicates that severe flattening occurred during the D2 stage, with a significant secondary non‐coaxial strain component along the W–E plane. This is associated with an eastward tectonic vergence, consistent with the subsequent D3 and D4 folding stages characterized by a dominant ENE tectonic transport. It is suggested that exhumation started from the D2 stage and continued during D3 at similar HP/LT metamorphic conditions. The widespread occurrence of unreacted lawsonite crystals suggests that exhumation was very fast and supports the idea that concurrent ductile deformation might play a role in its preservation.